International trade à la carte (Economic and Political Thought, 2015)
The new economic order emerging before our very eyes, resultingfrom the departure from the multilateral principles in favour of selectivesolutions is a consequence of the implementation of philosophy based onthe domination of particular elements over the common ones. Therefore,such solutions are selected which could be called à la carte, because theirchoice from the universal menu suits own interests of those who still havethe most to say in determining global rules. It concerns TFAs which joincountries which sometimes have quite divergent approaches to socioeconomicphilosophy and practical solutions in the field of economic policy.What binds them firmly, however, is the belief that they should abandon theburden of commitments within the WTO and follow a new path demarcatedby the TPP, TTIP or TiSA. The fact that it is really determined by the onewho currently has the greatest bargaining power is of course another issuethat can also be considered in terms of the balance of benefits and costs ofaccepting such a situation by weaker partners. As a result, we are dealingwith the atomisation of the world exchange in both subjective and directionalterms. This last issue in particular, in the context of the increasing role ofthe Pacific region in the global economy, is a good starting point for furtherconsiderations.